2021
DOI: 10.3389/fpsyt.2021.658340
|View full text |Cite
|
Sign up to set email alerts
|

Glymphatic Dysfunction: A Bridge Between Sleep Disturbance and Mood Disorders

Abstract: Mounting evidence demonstrates a close relationship between sleep disturbance and mood disorders, including major depression disorder (MDD) and bipolar disorder (BD). According to the classical two-process model of sleep regulation, circadian rhythms driven by the light–dark cycle, and sleep homeostasis modulated by the sleep–wake cycle are disrupted in mood disorders. However, the exact mechanism of interaction between sleep and mood disorders remains unclear. Recent discovery of the glymphatic system and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 153 publications
(152 reference statements)
0
30
0
Order By: Relevance
“…Numerous studies have shown that the glymphatic system exerts a significant effect on the distribution of a variety of substances in the brain, including not only its core waste clearance function but also the distribution and transport of nutrients such as glucose ( Lundgaard et al, 2015 ), some possible treatment substances (recombinant adeno-associated viral vectors) ( Murlidharan et al, 2016 ) and glial calcium signaling ( Rangroo Thrane et al, 2013 ). Because of its important physiological role, the glymphatic system is considered related to the occurrence and development of a variety of diseases ( Rasmussen et al, 2018 ), including neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, as well as mood disorders ( Yan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that the glymphatic system exerts a significant effect on the distribution of a variety of substances in the brain, including not only its core waste clearance function but also the distribution and transport of nutrients such as glucose ( Lundgaard et al, 2015 ), some possible treatment substances (recombinant adeno-associated viral vectors) ( Murlidharan et al, 2016 ) and glial calcium signaling ( Rangroo Thrane et al, 2013 ). Because of its important physiological role, the glymphatic system is considered related to the occurrence and development of a variety of diseases ( Rasmussen et al, 2018 ), including neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, as well as mood disorders ( Yan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al found 719 shared genes between MD and insomnia, which provide insight into the genetic substrates in depression individuals' comorbid insomnia symptoms ( 7 ). Yan et al proposed that dysfunctional glymphatic pathway may serve as a bridge between sleep disturbance and depression ( 8 ). In addition, sleep disturbance has been found to play a vital role in the development of depression ( 9 ), an increase risk for depression recurrence ( 10 ), poor response to antidepressant treatment ( 11 ), and suicidal ideation ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the acute phase of depression, brain regeneration and synaptic plasticity are compromised due to various reasons (e.g., dysregulated HPA-axis [ 43 ] and sleeping problems with reduced glymphatic brain clearance [ 44 ]). APOE ε4 allele carriers are additionally burdened by increased Aβ oligomer levels [ 7 , 8 ], which trigger depressive-like behavior as well as cognitive impairment [ 41 ] due to an influence on synaptic plasticity [ 39 ].…”
Section: Discussionmentioning
confidence: 99%